PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN DI UD. BERKAT JAYA KECAMATAN TELUKDALAM - Duha, Vilemon (Jurnal Ilmiah Mahasiswa Nias Selatan, 2024)
This research aims to determine the influence of price and service quality on purchasing decisions at UD. Thanks to Jaya. This type of research is a type of quantitative research that is causal in nature. The sample in this study amounted to 37 people. The analytical method used in this research is multiple linear regression analysis. The results of this research show that price and service quality variables influence purchasing decision variables. In this research, a multiple linear regression equation was obtained, namely: Y=10.202 + 0.409X1 + 0.434X2 and the Fcount value was (11.157) > Ftable value (3.259). Based on the results of this research and the discussion described, it can be concluded that price and service quality influence purchasing decisions at UD. Thanks to Jaya.There are several suggestions in this research, namely, 1) to UD. Thanks to Jaya for being able to provide prices that are lower than competitors' prices so that consumers make repeat purchases. 2) To meet consumer satisfaction, UD. Thanks to Jaya, we can provide good service to consumers, such as serving consumers in a friendly manner. 3) To retain customers, UD. Berkat Jaya provides stock of products that are often consumed by consumers. 3) So that consumers make repeated purchases, UD. Berkat Jaya provides product prices in accordance with product benefits and lower than competitors' prices while maintaining good service quality.